Written Green Human Resource Management Practices: Toward Sustainable Organizational Development - Tatasari, Titis; Yulfajar, Amrina (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to analyze the practice of Green Human Resource Management (GHRM) in supporting sustainable organizational development. GHRM refers to the integration of sustainability principles in human resource management functions, such as green recruitment, eco-friendly training, and ecology-based performance assessment. This study uses a qualitative approach with literature studies and case studies on several organizations that have implemented GHRM. The findings show that the practice of GHRM is able to increase employee environmental awareness, operational efficiency, and a positive organizational image. In addition, GHRM contributes significantly to the achievement of the Sustainable Development Goals (SDGs) through strengthening the organization's pro-environmental culture. The implications of this study emphasize the importance of the strategic role of the HR function in supporting the transition to an environmentally sound and long-term competitive organization.